Muscle‐specific changes in protein synthesis with aging and reloading after disuse atrophy. Issue 6 (16th July 2019) - Miller, Benjamin F.; Baehr, Leslie M.; Musci, Robert V.; Reid, Justin J.; Peelor, Frederick F.; Hamilton, Karyn L.; Bodine, Sue C.
Abstract: Background: Successful strategies to halt or reverse sarcopenia require a basic understanding of the factors that cause muscle loss with age. Acute periods of muscle loss in older individuals have an incomplete recovery of muscle mass and strength, thus accelerating sarcopenic progression. The purpose of the current study was to further understand the mechanisms underlying the failure of old animals to completely recover muscle mass and function after a period of hindlimb unloading. Methods: Hindlimb unloading was used to induce muscle atrophy in Fischer 344–Brown Norway (F344BN F1) rats at 24, 28, and 30 months of age. Rats were hindlimb unloaded for 14 days and then reloaded at 24 months (Reloaded 24), 28 months (Reloaded 28), and 24 and 28 months (Reloaded 24/28) of age. Isometric torque was determined at 24 months of age (24 months), at 28 months of age (28 months), immediately after 14 days of reloading, and at 30 months of age (30 months). During control or reloaded conditions, rats were labelled with deuterium oxide (D2 O) to determine rates of muscle protein synthesis and RNA synthesis. Results: After 14 days of reloading, in vivo isometric torque returned to baseline in Reloaded 24, but not Reloaded 28 and Reloaded 24/28. Despite the failure of Reloaded 28 and Reloaded 24/28 to regain peak force, all groups were equally depressed in peak force generation at 30 months. Increased age did not decrease muscle protein synthesis rates, and in fact, increased resting rates of protein synthesis were measured in the myofibrillar fraction (Fractional synthesis rate (FSR): %/day) of the plantaris (24 months: 2.53 ± 0.17; 30 months: 3.29 ± 0.17), and in the myofibrillar (24 months: 2.29 ± 0.07; 30 months: 3.34 ± 0.11), collagen (24 months: 1.11 ± 0.07; 30 months: 1.55 ± 0.14), and mitochondrial (24 months: 2.38 ± 0.16; 30 months: 3.20 ± 0.10) fractions of the tibialis anterior (TA). All muscles increased myofibrillar protein synthesis (%/day) in Reloaded 24 (soleus: 3.36 ± 0.11, 5.23 ± 0.19; plantaris: 2.53 ± 0.17, 3.66 ± 0.07; TA: 2.29 ± 0.14, 3.15 ± 0.12); however, in Reloaded 28, only the soleus had myofibrillar protein synthesis rates (%/day) >28 months (28 months: 3.80 ± 0.10; Reloaded 28: 4.86 ± 0.19). Across the muscles, rates of protein synthesis were correlated with RNA synthesis (all muscles combined, R 2 = 0.807, P < 0.0001). Conclusions: These data add to the growing body of literature that indicate that changes with age, including following disuse atrophy, differ by muscle. In addition, our findings lead to additional questions of the underlying mechanisms by which some muscles are maintained with age while others are not.